Pembrolizumab and trastuzumab in combination with FLOT in the perioperative treatment of HER2-positive, localized esophagogastric adenocarcinoma: a phase II trial of the AIO study group (AIO STO 0321) - Tintelnot, Joseph; Stein, Alexander; Batran, Salah-Eddin al-; Ettrich, Thomas J.; Götze, Thorsten; Grün, Barbara; Haag, Georg Martin; Heuer, Vera; Hofheinz, Ralf-Dieter; Homann, Nils; Bröring, Tobias Sebastian; Cruz, Mariana Santos; et al. (Frontiers in oncology, 2023)
Background: Esophagogastric adenocarcinoma (EGA) presents a substantial global health challenge as the number of cases continues to rise. The current standard approach for treating localized EGA involves a combination of triplet chemotherapy, which consists of a platinum compound, a fluoropyrimidine, and a taxane (known as FLOT), followed by surgery. In cases of metastatic EGA with HER2-positive status or in certain studies with localized EGA, the use of HER2-targeted antibodies such as trastuzumab has shown improved responses. Recently, the addition of programmed cell death protein 1 (PD-1) inhibitors, such as pembrolizumab, when combined with 5-FU, platinum-based chemotherapy, and trastuzumab, has demonstrated significant enhancements in response rates for HER2-positive metastatic EGA. However, there is currently insufficient evidence regarding this treatment approach in localized HER2-positive disease.MethodsThe PHERFLOT study is an open-label, single-arm, multicenter, exploratory phase II trial designed to assess the efficacy, safety, and tolerability of perioperative pembrolizumab, FLOT, and trastuzumab in patients with previously untreated localized HER2-positive EGA. In total, 30 patients will be recruited. The co-primary end points are pathological complete response rate and disease-free survival rate after 2 years. Secondary objectives include safety and tolerability, efficacy in terms of progression-free survival and objective response rate and translational markers, such as blood-based signatures (e.g., immune repertoire changes or emergence of anti-HER2 resistance variants) or microbiota signatures that may correlate with immune activation and therapy response.DiscussionRecent evidence from phase II clinical trials demonstrated improved efficacy through the addition of trastuzumab to perioperative FLOT. Furthermore, in advanced or metastatic EGA, the combination of trastuzumab, FLOT, and the PD1-inhibitor pembrolizumab significantly improved treatment response. The PHERFLOT study aims to assess the efficacy and safety of this treatment approach in HER2-positive-localized EGA, potentially identifying a promising new perioperative regimen for localized EGA, which then needs to be confirmed within a randomized trial. Furthermore, the accompanying translational program of the study might help to improve the stratification of suitable patients and to identify potential translational targets for future clinical trials.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT05504720.